DESIGN AND FABRICATION OF CRANIOPLASTY PROSTHESES: FIT EVALUATION BETWEEN PHANTOM-BASED HAPTIC ENVIRONMENT AND MATERIALISE 3-MATIC SOFTWARE - H., Hasib; S.H., Yahaya; M.A., Kamely; A.Y., Bani Hashim; A.M.M., Najib; S.S., Simha (Journal of Advanced Manufacturing Technology (JAMT), 2014)
Two different design methods for customized cranioplasty prostheses are presented in this paper. The first approach is designing the digital model of the cranial implants in a haptic environment, utilizing a combination of a PHANToM haptic device and a freeform software called Claytools. The other method makes use of a software solution provided by Materialise Inc. known as 3-matic. Next, the skull models and the designed implants are fabricated via stereolitography (SLA). Finally, the implants’ fit over the skull models are evaluated to determine the most accurate method.